Nové postupy v pivovarnictví - Mareš, Pavel; Pavel Mareš (České vysoké učení technické v Praze, 2021)
Práce představuje postupy a technologii vaření piva. Následně představuje vybrané moderní postupy v pivovarnictví (studené chmelení, náhražky sladu, vaření bezlepkových piv). Dále se práce věnuje technické realizaci dynamických metod studeného chmelení. Výstupem práce je basic design chmelového extraktoru pro malý pivovar o zadaném obejmu výroby.

In this thesis traditional process of beer brewing is breafly introduced. Followed by resarch on novel trends in brewing (such as dry hopping, malt alternatives and gluten-free beer brewing). In the main part of thesis technical implementation of dynamic methods of dry hopping are presented. Basic design of hop extractor is expected to be a result of the thhesis.
Novel trends in Brewing
Keywords: pivo; chmelový extraktor; studené chmelení; beer; hop extractor; dry hopping